Natural and Induced T Regulatory Cells in Cancer - Adeegbe, Dennis O.; Nishikawa, Hiroyoshi (Frontiers in Immunology, 2013)
CD4+Foxp3+ T regulatory (Treg) cells control many facets of immune responses ranging from autoimmune diseases, to inflammatory conditions, and cancer in an attempt to maintain immune homeostasis. Natural Treg (nTreg) cells develop in the thymus and constitute a critical arm of active mechanisms of peripheral tolerance particularly to self-antigens. A growing body of knowledge now supports the existence of induced Treg (iTreg) cells which may derive from a population of conventional CD4+ T cells. The fork-head transcription factor (Foxp3) typically is expressed by natural CD4+ Treg cells, and thus serves as a marker to definitively identify these cells. On the contrary, there is less consensus on what constitutes iTreg cells as their precise definition has been somewhat elusive. This is in part due to their distinct phenotypes which are shaped by exposure to certain inflammatory or “assault” signals stemming from the underlying immune disorder. The “policing” activity of Treg cells tends to be uni-directional in several pathological conditions. On one end of the spectrum, Treg-cell suppressive activity is beneficial by curtailing T cell response against self-antigens and allergens thus preventing autoimmune diseases and allergies. On the other end however, their inhibitory roles in limiting immune response against pseudo-self antigens as in tumors often culminates into negative outcomes. In this review, we focus on this latter aspect of Treg-cell immunobiology by highlighting the involvement of nTreg cells in various animal models and human tumors. We further discuss iTreg cells, relationship with their natural counterpart, and potential co-operation between the two in modulating immune response against tumors. Lastly, we discuss studies focusing on these cells as targets for improving anti-tumor immunity.